Notices
Results 1 to 8 of 8

Thread: A question.

  1. #1 A question. 
    New Member
    Join Date
    Sep 2005
    Location
    Vedai,India
    Posts
    3
    Will 4=5.

    My maths teacher proved this in my class when I was in high school.
    How come it is possible.


    Reply With Quote  
     

  2.  
     

  3. #2  
    Forum Radioactive Isotope cosmictraveler's Avatar
    Join Date
    May 2005
    Location
    Key West, Florida, Earth
    Posts
    4,789
    I guess you should ask your maths teacher because I see that you didn't learn from when the maths teacher taught you how its done.


    Reply With Quote  
     

  4. #3  
    Forum Freshman
    Join Date
    Sep 2005
    Posts
    19
    Hmmm...

    I can prove 1=2

    Let x = y

    x(x - y) = x^2 - xy

    but x=y

    x(x - y) = x^2 - y^2

    x (x - y) = (x + y)(x - y)

    Divide by (x - y)

    x = x + y

    but x=y

    Therefore x = x + x

    x = 2x

    1=2

    Wow happy days 1=2, now all sorts of strange stuff can happen....
    I can't remember which mathematician did this but I'm sure someone will enlighten us.
    He proved that if 1=2 you could prove anyone was the pope.
    i.e. Fact 1: John and the pope are 2. Fact 2: 1=2 therefore we can deduce that John and the pope are 1.

    Now where is the problem with our maths.....

    Well the problem is when we divide by (x - y), as x - y = 0 and we cannot divide by 0

    I'm not sure how your teacher proved that 4=5 but you can see that 4*(0)=5*(0) [i.e. 0=0] and you cannot divide by 0 so I'm sure he did it in a similar way to the 1=2.
    Reply With Quote  
     

  5. #4  
    Forum Freshman
    Join Date
    Aug 2005
    Posts
    6
    1 will not ever equal 2 if you graph it the slops are both 0 so the lines will never intersect. Unless, you add a variable like X, but then it would not read 1=2.
    Reply With Quote  
     

  6. #5  
    Forum Freshman
    Join Date
    Sep 2005
    Posts
    19
    How are you plotting 1=2?

    If you are plotting x=1 and x=2 then you would have two lines with infinte slope, and of course they would never come into contact unless you folded the x-y plane to make it happen

    In my last post I just pointed out that 1 * (0) = 2 * (0)
    Reply With Quote  
     

  7. #6  
    Forum Freshman
    Join Date
    Aug 2005
    Posts
    6
    you can graph 1 and 2 on a graphing calculator like the TI-83 or TI-92 by puting y1=1 and y2=2. Also, I agree with you that 1 * (0) = 2 * (0).
    Reply With Quote  
     

  8. #7  
    Forum Freshman
    Join Date
    Dec 2005
    Location
    India
    Posts
    65
    Let a=b=1

    Therfore a*a=ab
    a*a-b*b=ab-bb
    a*a-b*b=b(a-b)
    (a+b)(a-b)=b(a-b)
    a+b=b
    2=1 (since a=b=1)
    2+3=1+3
    5=4

    :wink:
    Reply With Quote  
     

  9. #8  
    Forum Masters Degree invert_nexus's Avatar
    Join Date
    Apr 2005
    Posts
    638
    As Mobius said, his version of the proof is dependent upon a stage where you divide by zero. This should stop the calculation at this point, but to one who isn't paying proper attention or may not be that educated in math, the proof seems valid.

    I had a physics teacher that showed me an equation proving 1=-1. I always had these visions of antimatter in my head with that one. Imagine the dismay when I learned the vile trick used to perpetrate such a sham.

    Meh.

    Anyway.
    Here's some other erroneous proofs I dug up for a similar thread in some long ago.

    Theorem : 3=4
    Proof:
    Suppose:
    a + b = c
    This can also be written as:
    4a - 3a + 4b - 3b = 4c - 3c
    After reorganising:
    4a + 4b - 4c = 3a + 3b - 3c
    Take the constants out of the brackets:
    4 * (a+b-c) = 3 * (a+b-c)
    Remove the same term left and right:
    4 = 3


    Theorem : All numbers are equal to zero.
    Proof: Suppose that a=b. Then
    a = b
    a^2 = ab
    a^2 - b^2 = ab - b^2
    (a + b)(a - b) = b(a - b)
    a + b = b
    a = 0


    Theorem: 1$(dollar) = 1c(cent).
    Proof:
    And another that gives you a sense of
    money disappearing...
    1$ = 100c
    = (10c)^2
    = (0.1$)^2
    = 0.01$
    = 1c


    Theorem: 1 = -1 .
    Proof:
    1/-1 = -1/1
    sqrt[ 1/-1 ] = sqrt[ -1/1 ]
    sqrt[1]*sqrt[1] = sqrt[-1]*sqrt[-1]
    ie 1 = -1


    Theorem: 4 = 5
    Proof:
    16 - 36 = 25 - 45
    4^2 - 9*4 = 5^2 - 9*5
    4^2 - 9*4 + 81/4 = 5^2 - 9*5 + 81/4
    (4 - 9/2)^2 = (5 - 9/2)^2
    4 - 9/2 = 5 - 9/2
    4 = 5
    Reply With Quote  
     

Bookmarks
Bookmarks
Posting Permissions
  • You may not post new threads
  • You may not post replies
  • You may not post attachments
  • You may not edit your posts
  •